Mindfulness and academic resilience among unprivileged college students: The mediating role of self-compassion - Hanan Salsabila; Pratiwi Widyasari (HUMANITAS: Indonesian Psychological Journal, 2021)
A growing body of studies shows that the higher individuals' education level, the higher their chance of getting a better salary. Unfortunately, for unprivileged students who want to improve their living conditions, the risk of failure to complete college is much higher because of numerous obstacles regarding their economic status. Having good academic resilience may foster unprivileged college students to achieve success in their studies. This study aimed to find out the relationship between mindfulness and academic resilience with self-compassion as a mediator. One hundred thirty-one unprivileged college students participated in this cross-sectional, quantitative study. Three adapted scales were used: (1) The Mindfulness Attention Awareness Scale (MAAS), (2) The Self-Compassion Scale (SCS), and (3) The Academic Resilience Scale (ARS-30). The data were then analyzed with the Hayes Regression technique. The findings support the hypothesis that self-compassion fully mediates the relationship between mindfulness and academic resilience among unprivileged Indonesian college students with a 23.1 percent contribution. Therefore, among unprivileged students, the impact of mindfulness on academic resilience will be higher through self-compassion.